Antidepressant and QT interval prolongation, how should we look at this issue? Focus on citalopram. (February 2014) - Pae, Chi-Un; Wang, Sheng-Min; Lee, Soo-Jung; Han, Changsu; Patkar, Ashiwn A; Masand, Prakash S
Abstract : Introduction: Evidence increasingly points to the potential development of harmful cardiac side effects concomitant with the use of a number of psychotropic drugs, primarily traditional antipsychotics and tricyclic antidepressants. Areas covered: The US Food and Drug Administration announced safety warnings associated with the use of citalopram with QT interval prolongation in 2011 and 2012. This paper explores the clinical background of QT interval prolongation, clinical data related to antidepressants and QT interval prolongation, the clinical implications of safety issues associated with the use of antidepressants and future research directions. Expert opinion: Currently available evidence proposes that citalopram may not be definitely associated with the increase of cardiac mortality, although it should be related with increase of QT prolongation. A firm consensus regarding the cardiac safety issues associated with antidepressants has to be established in near future. Hence, the choice of an individual antidepressant regarding cardiac safety issues should be based on multiple factors; clinicians may need to select the best available antidepressant for each individual based on that patient's vulnerability, the proven efficacy and safety of each agent and a reasonable benefit:risk ratio, based on currently available findings.